1994
DOI: 10.1152/ajpgi.1994.266.3.g363
|View full text |Cite
|
Sign up to set email alerts
|

Tyrphostins inhibit secretagogue-induced 1,4,5-IP3 production and amylase release in pancreatic acini

Abstract: We examined the role of protein tyrosine kinase inhibitors (tyrphostins) in secretagogue-induced inositol 1,4,5-trisphosphate (1,4,5-IP3) production and amylase secretion in rat pancreatic acinar cells. The data show that various specific cell-permeant tyrphostins (methyl 2,5-dihydroxycinnamate, tyrphostin 25, and genistein) inhibited the cholecystokinin octapeptide-, carbachol-, and bombesin-induced 1,4,5-IP3 production and amylase release. In digitonin-permeabilized cells, tyrphostins decreased 1,4,5-IP3 acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1995
1995
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…It is known that certain tyrosine residues in InsP3 receptors can be phosphorylated (Harnick, Jayaraman, Ma, Mulieri, Go & Marks, 1995). Thus it is possible that InsP3 action is report of tyrphostins interfering with the production of InsP3 (in pancreatic acinar cells in response to carbachol and cholecystokinin octapeptide (Piiper et al 1994)). Thus, it is possible that protein tyrosine phosphorylation influences the efficacy of mGluR-mediated activation of InsP3 production.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that certain tyrosine residues in InsP3 receptors can be phosphorylated (Harnick, Jayaraman, Ma, Mulieri, Go & Marks, 1995). Thus it is possible that InsP3 action is report of tyrphostins interfering with the production of InsP3 (in pancreatic acinar cells in response to carbachol and cholecystokinin octapeptide (Piiper et al 1994)). Thus, it is possible that protein tyrosine phosphorylation influences the efficacy of mGluR-mediated activation of InsP3 production.…”
Section: Methodsmentioning
confidence: 99%
“…Effect of Pervanadate on Phospholipase C Activity-Previous reports on rat pancreatic acinar cells suggest that tyrosine kinases are involved in the activation of phospholipase C induced by different secretagogues such as cholecystokinin, bombesin, or carbachol (12,13). To test if pervanadate-stimulated amylase secretion is induced by pervanadate-mediated activation of phospholipase C, AR4-2J cells were treated with 100 M or 1 mM pervanadate for 10 s to 50 min and with 10 nM bombesin for 15 s for comparison.…”
Section: Fig 5 Effect Of Genistein and Tyrphostin B56 On Bombesin-omentioning
confidence: 99%
“…It was suggested that tyrosine phosphorylation could amplify the secretory response rather than provide an obligate signal for enzyme secretion. On the other hand, tyrosine kinase inhibitors such as genistein and tyrphostin 25 were shown to inhibit agonist-induced amylase secretion and phospholipase C activation in rat pancreatic acinar cells (12,13), indicating that tyrosine kinases are involved in receptor-mediated stimulation of amylase secretion.…”
mentioning
confidence: 99%
“…These results suggest that genistein inhibits amylase exocytosis through the inhibition of protein tyrosine phosphorylation. In pancreatic acini, however, genistein markedly inhibited amylase release evoked by Ca, but not by phorbol ester or cAMP [4][5][6], indicating that the inhibitory effect of genistein is strictly selective concerning secretory stimuli and cells. It is presently unknown why genistein is able to inhibit cAMPmediated amylase release in parotid acini but not in pancreatic ones.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ca2+-mobilizing agonists such as cholecystokinin and acetylcholine mainly stimulate amylase release from pancreatic acini, and Ca and protein kinase C seem to be equally important in the regulatory mechanism [3]. However, it was recently found that cholecystokinin and carbachol increased protein tyrosine phosphorylation in addition to serine/threonine phosphorylation and that tyrosine kinase inhibitors, including genistein, significantly inhibited amylase release stimulated by those agonists [4][5][6][7]. These results suggest that tyrosine kinases are involved in the regulation of amylase exocytosis from pancreatic acini.…”
Section: Introductionmentioning
confidence: 99%